Nepal : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Poverty in Nepal remains pervasive owing to insufficient growth and inadequate targeting under the poverty alleviation programs. Executive Directors stressed the need to implement strong fiscal and monetary policies and accelerate structural reforms. They welcomed the Poverty Reduction Strategy Paper (PRSP), social sector development, targeted programs for the poor and deprived groups, and improved governance. They emphasized the need to improve revenue mobilization, prioritize spending, and contain domestic borrowing for economic growth.